Nutritional status assessment and occurence of complications in patients after gastrectomy - Ścisło, Lucyna; Walewska, Elżbieta; Kłęk, Stanisław; Szczepanik, Antoni; Orzeł-Nowak, Anita; Czupryna, Antoni; Kulig, Jan (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Background. Malnutrition is a frequent consequence of cancer, especially stomach cancer. The implication of malnutrition are immune system disorder and increased risk of complications, particularly postoperative. The increased number of complications causes longer hospitalization and extension of treatment cost. Therefore, early recognition of malnutrition in perioperative period has a significant influence on the postoperative complications decrease. Aim of the study. The assessment of the nutritional status in stomach cancer patients classified for surgery influence on the occurrence of complications after gastrectomy. Material and methods. The study included 99 perioperative patients with stomach cancer. Nutritional status was evaluated with screening method on the basis of Thorsdottir’s test, percentage body mass loss, serum albumin concentration, the total count of peripheral blood lymphocytes (PBL). Results. In preoperative stomach cancer patients the decrease of serum albumin concentration and of the total count of PBL occurred. Generally 50,5% of the examined fulfilled the malnutrition standards detected with screening method. On the grounds of the total count of PBL the researches detected 43,1% malnourished patients, whereas on the grounds of serum albumin concentration — 17,1% of the examined. The decrease of the serum albumin concentration, the total count of lymphocytes and body mass was observed in the postoperative period. In malnourished patients occurred more complications of pneumonia (25,8% vs. 17,7%), disorders of respiratory (9,7% vs. 2,9%) and circulatory system (12,9% vs. 0,0%). Conclusions. Gastrectomy intensifies malnutrition. Comparing to the group of the properly nourished, in the malnourished patients more complications of respiratory and circulatory system was observed.